On the evolution of household income - Giambattista Salinari; Gustavo De Santis (Luxembourg Income Study (LIS), 2008)
We present a markovian homogeneous model that mimics the evolution of household income. With three parameters only, the model generates a set of theoretical curves that closely fit actual income distributions, as observed in 19 advanced economies in the period 1967-2004. The fit is better, and theoretically more consistent, than that obtained with other models customarily used in the literature, for instance log-normal or power-law models.
Keywords: 330; Haushaltseinkommen; Einkommensverteilung; Mikroökonomische Fundierung; Markovscher Prozess; OECD-Staaten